RECENT STUDIES OF TICK-BORNE INFECTIONS IN MONGOLIA - D. Anu; H. Sung-Hee; L. Sang-Eun; L. Won-Ja; D. Abmed; D. Nyamkhuu; P. Nymadawa (Acta Biomedica Scientifica, 2018)
We have aimed to detect both Rickettsiae species and Babesia microti in adult ticks of Dermacentor nutalli in Tuv province; and  looked for only Rickettsiae species in Ixodes persulcatus in Selenge  province. Using the PCR and DNA sequencing techniques, we  amplified and sequenced the 16S rRNA, gltA, rOmpA genes of  Rickettsia and 18S rRNA gene of B. microti and Rickettsia species  were identified. Infection rate for Rickettsiae spp. was 82.7 %  (115/139 samples) by 16S rRNA sequencing results and among  them the highest prevalence rate was that for R. raoultii strain –  71.4 % (80/111 samples) by gltA gene sequencing and 100 %  (81/81 samples) by rOmpA gene sequencing. Canditatus Rickettsia tarasevichiae strain was detected in 27.9 % (31/11  samples) by gltA gene sequencing. Infection rate for Rickettsiae spp. in D. nutalli ticks was 84.3 % (81/96 samples) and R. raoultii  strain comprised 96.2–98.7 % among them. Adult ticks of I.  persulcatus were infected with Rickettsiae spp. with 78 % and 93.75  % of them were R. raoultii strain. Seventeen out of 97 ticks (17.5  %) were found to be infected with B. microti. Nucleotide DNA  sequencing of partial 18S rRNA and gltA genes supported the PCR  results. We have identified that the same species of ticks commonly  distributed in Mongolia have been infected with R. sibirica, R. raoultii  and B. microti. It might be the strength of our study as B.  microti have not been detected in D. nuttalli ticks yet. We are  considering to detect the tick-borne infections in humans.